Preparation and performance of plastic scintillators with copper iodide complex-loaded for radiation detection. (17th May 2022) - Li, Wen; Li, Yunyun; Nikl, Martin; Hamel, Matthieu; Wu, Hongshu; Qian, Sen; Kucerkova, Romana; Babin, Vladimir; Ren, Guohao; Wu, Yuntao
Abstract: The development of plastic scintillators loaded with low-cost phosphorescent sensitizer is currently an important topic toward enhancing the scintillation light yield for radiation detection applications. In this work, we report plastic scintillators loaded with deep-blue-emitting phosphorescent sensitizer CuI(PPh3 )2 ( t -BuPy), where PPh3 and t -BuPy stand for triphenylphosphine and 4- tert -butylpyridine, respectively. CuI(PPh3 )2 ( t -BuPy)-loaded poly(vinyltoluene)-based plastic scintillators with high optical transmittance of over 80% were synthesized via bulk polymerization method. The optical absorption, photoluminescence spectra, decay kinetics, and scintillation performance under X-ray, γ-ray, and α-particle excitation were comprehensively investigated. The scintillation yield was reduced with the increase of CuI(PPh3 )2 ( t -BuPy) loading concentration. The physical mechanism and the role of the copper iodide complex in scintillation yield reduction are proposed. Graphical abstract: Image 1 Highlights: Poly(vinyltoluene)-based plastic scintillators loaded with phosphorescent sensitizer CuI(PPh3 )2 ( t -BuPy) were synthesized. The scintillation yield of PVT scintillators is reduced with the increase of CuI(PPh3 )2 ( t -BuPy) loading concentration. The scintillation yield reduction is associated with the nonradiative dissipation of energy from CuI(PPh3 )2 ( t -BuPy). Plastic scintillator containing only CuI(PPh3 )2 ( t -BuPy) showed α/γ PSD performance.